INNOVATIVE SUPPORT FOR INSTRUCTION IN INFORMATION AND LIBRARY STUDIES AT QUEENSLAND UNIVERSITY OF TECHNOLOGY - Middleton, Michael; Hallam, Gillian; Partridge, Helen (Malaysian Journal of Library and Information Science, 2003)
A description is provided of the variety of mechanisms for instructional support that are used in library and information studies programmes at Queensland University of Technology. These include the use of various facilities within the University’s online teaching system. Along with assessment initiatives such as professional portfolios, integration within the teaching framework of a supplementary instruction scheme, and increased attention to generic capabilities, these have enhanced instructional support